Smart NEA Class / Nurul Ezaili Alias and Rozana Othman - Alias, Nurul Ezaili; Othman, Rozana (Division of Research and Industry Linkages, 2017)
Malaysia's development plan for education, as laid out in the Malaysian Education Blueprint 2013-2025, is in line with the direction o f the 2050 National Transformation (TN50) vision. TN50 w ill bring about many changes in ensuring a strong education framework for the people that would mould the coming generations. Smart phones, nowadays, everyone has one or at least wants one including teachers and students. Mobile App is also found to be the most important development in innovating the teaching and learning (T&L) skills. A "Smart T&L" should never be defined as just conventional classrooms. In current T&L practices, teachers usually update their T&L activities through provided e-learning web-based by the institution. Traditionally, student has to access to their university's e-learning web-based account in order to continuously get information from the teacher. However, this existing practice facing a difficulty in sending and receiving real-time updates from teachers and students, respectively. Further, the difficulty mentioned above can be solved by using this T&L innovation where student will receive information automatically (real-time) through their Smartphone. Therefore, the objectives of this innovation is (1) to use technology as an innovative medium in T&L; (2) to develop a T&L Mobile A pp that consist of variety features into one platform; (3) to create a higher engagement between teacher and student at any time. “NEA Class” Mobile App is developed by using AppDolph Platform, Advanced features in "NEA Class” enables teacher to engage with students easily, effectively and efficiently. As a conclusion, "NEA Class” (offered features of Teacher's Wall, Smart Attendance, Smart Absence Form, Push Notification/Announcement, Notes and Tutorial and Assignment) is used to accommodate the needs of students who use adaptive technology in their daily life. "NEA Class" is believed to give a new breath in keeping students engaged with their lecturers all the time without any difficulties.